The non-invasive serum biomarker soluble Axl accurately detects advanced liver fibrosis and cirrhosis - Staufer, Katharina (Cell Death Dis, 2017)
Soluble Axl (sAxl) was recently shown to be strongly released into the blood during liver fibrogenesis and hepatocellular carcinoma suggesting sAxl as a biomarker of liver diseases. In this study we are the first to evaluate sAxl in human serum in comparison to Enhanced Liver Fibrosis (ELF) test and transient elastography (TE; Fibroscan) for its value to detect significant (F≥2), advanced fibrosis (F≥3), and cirrhosis (F4) in different liver disease etiologies and healthy controls. To properly determine the diagnostic accuracy of sAxl, a test cohort as well as a validation cohort was employed using liver biopsy as a reference method. Most notably, sAxl was confirmed to be an accurate biomarker of liver fibrosis and cirrhosis. Its accuracy was increased, if total serum albumin was added to build a sAxl/albumin ratio. Thereby an AUC of 0.763, 0.776, 0.826, and 0.832 was achieved corresponding to histological fibrosis stages F≥2, F≥3, F4 with liver biopsy as a reference method, and cirrhosis according to imaging techniques, respectively. With a cut-off of 1.29, a sensitivity, specificity, PPV, and NPV of 78.5%, 80.1%, 44%, 94.9% for the detection of cirrhosis was achieved. In comparison, ELF test and TE showed an AUC of 0.910, and 0.934, respectively, for the detection of cirrhosis. However, performance of TE was not possible in 14.4% of patients and both, ELF™ test and TE bear the disadvantage of high costs. In conclusion, the sAxl/albumin ratio is suggested as an accurate biomarker of liver fibrosis and cirrhosis. Due to its easy applicability and low costs it is suitable as screening parameter for significant to advanced liver fibrosis and cirrhosis, especially if TE is not available or not applicable.